Aspirin Enhances Osteogenic Potential of Periodontal Ligament Stem Cells (PDLSCs) and Modulates the Expression Profile of Growth Factor–Associated Genes in PDLSCs. Issue 7 (1st July 2016) - Abd Rahman, Fazliny; Mohd Ali, Johari; Abdullah, Mariam; Abu Kasim, Noor Hayaty; Musa, Sabri
Abstract : Background: This study investigates the effects of aspirin (ASA) on the proliferative capacity, osteogenic potential, and expression of growth factor–associated genes in periodontal ligament stem cells (PDLSCs). Methods: Mesenchymal stem cells (MSCs) from PDL tissue were isolated from human premolars (n = 3). The MSCs' identity was confirmed by immunophenotyping and trilineage differentiation assays. Cell proliferation activity was assessed through 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay. Polymerase chain reaction array was used to profile the expression of 84 growth factor–associated genes. Pathway analysis was used to identify the biologic functions and canonic pathways activated by ASA treatment. The osteogenic potential was evaluated through mineralization assay. Results: ASA at 1, 000 μM enhances osteogenic potential of PDLSCs. Using a fold change (FC) of 2.0 as a threshold value, the gene expression analyses indicated that 19 genes were differentially expressed, which includes 12 upregulated and seven downregulated genes. Fibroblast growth factor 9 (FGF9), vascular endothelial growth factor A ( VEGFA ), interleukin‐2, bone morphogenetic protein‐10, VEGFC, and 2 ( FGF2 ) were markedly upregulated (FC range, 6 to 15), whereas pleotropin, FGF5, brain‐derived neurotrophic factor, and Dickkopf WNT signaling pathway inhibitor 1 were markedly downregulated (FC 32). Of the 84 growth factor–associated genes screened, 35 showed high cycle threshold values (≥35). Conclusions: ASA modulates the expression of growth factor–associated genes and enhances osteogenic potential in PDLSCs. ASA upregulated the expression of genes that could activate biologic functions and canonic pathways related to cell proliferation, human embryonic stem cell pluripotency, tissue regeneration, and differentiation. These findings suggest that ASA enhances PDLSC function and may be useful in regenerative dentistry applications, particularly in the areas of periodontal health and regeneration.